Comparison of two CT-based methods for tibial bone mineral density assessment and their associations with bone and eggshell traits in laying hens - da Silva, Webert Aurino; Rabello, Carlos Bôa-Viagem; de Souza, Lilian Francisco Arantes; de Oliveira, Elton Francisco; Santos, Adrielle Carneiro Araújo; de Pádua Ferreira Santos, Leanndra; Ribeiro, Apolonio Gomes; dos Santos Nascimento, Júlio Cézar; dos Santos, Marcos José Batista; Carvalho, Lucas Rannier Ribeiro Antonino; Costa, Fabiano Sellos (Frontiers in Veterinary Science, 2025)
IntroductionBone quality is essential for the health, welfare, and productivity of laying hens. Quantitative computed tomography (QCT) allows accurate evaluation of bone mineral density (BMD), but methodological differences may influence the reliability of results. This study compared two QCT-based methodologies for tibial BMD assessment and investigated their associations with bone composition and eggshell quality traits.MethodsForty-eight 48-week-old Dekalb White hens were evaluated. Method 1 (M1) measured BMD in four predefined cortical quadrants used as regions of interest. Method 2 (M2) applied semi-automatic segmentation of the entire bone area using predefined density thresholds. BMD results were compared between methods, and correlations were calculated with bone composition (bone weight and volume) and eggshell quality (shell weight, thickness, and breaking strength).ResultsThe methods showed moderate correlation (r = 0.6822, p < 0.001) but low concordance (CCC = 0.120), with M1 consistently overestimating BMD. Mean BMD values were 1152.49 ± 218.54 mgHA/cm3 for M1 and 711.22 ± 118.40 mgHA/cm3 for M2. M1 demonstrated weak correlations with bone parameters (bone weight: R2 = 0.423, p = 0.038; bone volume: R2 = 0.086, p = 0.043) and minimal associations with eggshell traits. In contrast, M2 showed stronger relationships with bone composition (bone weight: R2 = 0.789, p = 0.003; bone volume: R2 = 0.535, p = 0.010) and significant negative correlations with eggshell weight (R2 = –0.741, p = 0.009), thickness (R2 = –0.617, p = 0.017), and breaking strength (R2 = –0.654, p = 0.048).DiscussionM2 provided more accurate, consistent, and biologically meaningful BMD estimates than M1. Its stronger associations with bone and eggshell parameters support the adoption of M2 as a reliable QCT-based methodology for evaluating bone quality in laying hens.